The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/5479007
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Research on Microseismic Source Location Method Based on Waveform Characteristics Monitored by Nanomaterial Sensor under the Background of Metal Oxide Polluted Environment

Abstract: In recent years, the monitoring range of source location technology has developed from being one-dimensional and two-dimensional to being three-dimensional. However, due to the complexity and nonuniformity of the seismic wave propagation medium and the uncertainty of the propagation law, there will be large errors in the source location results. Therefore, the analysis of vibration signal has become the key problem of current research. This paper designs a microseismic monitoring system based on Internet of Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Natural nanoparticle manufacturing techniques based on microbes, enzymes, fungi, and flowers derived from plants were proposed as ecologically sound replacements for chemical and physical approaches. Manufacturing nanoparticles using plants or plant components might sometimes be beneficial over other biological methods because it eliminates the complex procedures of sustaining bacterial culture [20]. Since Al 2 O 3 NPs were chemically bio-inert and hydrogel was more durable, they have received exceptional interest in the leading edge of specialized development in the synthesis and development of contemporary antibacterial drugs with sustainable biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Natural nanoparticle manufacturing techniques based on microbes, enzymes, fungi, and flowers derived from plants were proposed as ecologically sound replacements for chemical and physical approaches. Manufacturing nanoparticles using plants or plant components might sometimes be beneficial over other biological methods because it eliminates the complex procedures of sustaining bacterial culture [20]. Since Al 2 O 3 NPs were chemically bio-inert and hydrogel was more durable, they have received exceptional interest in the leading edge of specialized development in the synthesis and development of contemporary antibacterial drugs with sustainable biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%